Feasibility Study of HIV Sentinel Surveillance using PMTCT data in Cameroon: from Scientific Success to Programmatic Failure. Issue 1 (December 2017) - Billong, Serge; Dee, Jacob; Fokam, Joseph; Nguefack-Tsague, Georges; Ekali, Gabriel; Fodjo, Raoul; Temgoua, Edith; Billong, Edson-Joan; Sosso, Samuel; Mosoko, Jembia; Monebenimp, Francisca; Ndjolo, Alexis; et al.
Abstract Background In low-income countries (LICs), HIV sentinel surveillance surveys (HIV-SSS) are recommended in between two demographic and health surveys, due to low-cost than the latter. Using the classical unlinked anonymous testing (UAT), HIV-SSS among pregnant women raised certain ethical and financial challenges. We therefore aimed at evaluating how to use prevention of mother-to-child transmission of HIV (PMTCT) routine data as an alternative approach for HIV-SSS in LICs. Methods A survey conducted through 2012 among first antenatal-care attendees (ANC1) in the ten regions of Cameroon. HIV testing was performed at PMTCT clinics as-per the national serial algorithm (rapid test), and PMTCT site laboratory (PMTCT-SL) performances were evaluated by comparison with results of the national reference laboratory (NRL), determined as the reference standard. Results Acceptance rate for HIV testing was 99%, for a total of 6521 ANC1 (49 · 3% aged 15–24) enrolled nationwide. Among 6103 eligible ANC1, sensitivity (using NRL testing as the reference standard) was 81 · 2%, ranging from 58 · 8% (South region) to 100% (West region); thus implying that 18 · 8% HIV-infected ANC1 declared HIV-negative at the PMTCT-SL were positive from NRL-results. Specificity was 99 · 3%, without significant disparity across sites. At population-level, this implies that every year in Cameroon, 2, 500 HIV-infected women are wrongly declared seronegative, while 1, 000 are wrongly declared seropositive. Only 44 · 4% (16/36) of evaluated laboratories reached the quality target of 80%. Conclusions The study identified weaknesses in routine PMTCT HIV testing. As Cameroon transitions to using routine PMTCT data for HIV-SSS among pregnant women, there is need in optimizing quality system to ensure robust routine HIV testing for programmatic and surveillance purposes.